Decompressive surgery form malignant middle cerebral artery infarctions (Annals of Medical Research, 2021)
Aim: The aim of the study is to evaluate patients who underwent decompressive surgery followed by malignant MCA infarction diagnosis in our center and compare and discuss our results with the current literature.
Keywords: Stroke; Malignant MCA İnfarction; Decompressive Surgery